Q1. Solve the system of equationd by addition method.
-2x+y=6
-3x-4y=20
Select the correct choice below and, if necessary, fill in the answer box to comlete your choice
a)The solution is__(simplify your answer. type an ordere pair)
b) Infinitely many solutions
c) No Solution
Q2. Solve the system of equationd by addition method.
6x+4y=-10
2x-4y=-30
Select the correct choice below and, if necessary, fill in the answer box to comlete your choice
a)The solution is__(simplify your answer. type an ordere pair)
b) Infinitely many solutions
c) No Solution
Q3. Solve the system of equationd by addition method.
2x+4y=7
4x+8y=0
Select the correct choice below and, if necessary, fill in the answer box to comlete your choice
a)The solution is__(simplify your answer. type an ordere pair)
b) Infinitely many solutions
c) No Solution
Q4. Solve the system of equationd by addition method.
-2x=-2y-8
-4x+2y=-16
Select the correct choice below and, if necessary, fill in the answer box to comlete your choice
a)The solution is__(simplify your answer. type an ordere pair)
b) Infinitely many solutions
c) No Solution
Q5. Solve the system of equationd by addition method.
-3x-5y=7
5x+15y=7
The solution is ___
Q6. Solve the system of equationd by addition method.
(x/2)-(y/6)=-1
(x/4)+(y/12)=-3
Select the correct choice below and, if necessary, fill in the answer box to comlete your choice
a)The solution is__(simplify your answer. type an ordere pair)
b) Infinitely many solutions
c) No Solution
Q7. Solve the system of equationd by addition method.
(x/7)-y=2
-(x/2)+(7y/2)=-7
Select the correct choice below and, if necessary, fill in the answer box to comlete your choice
a)The solution is__(simplify your answer. type an ordere pair)
b) Infinitely many solutions
c) No Solution
Q8.Solve the system of equationd by addition method or the substitution method
x+(1/20y)=(1/4)
3x+2y=2
The solution is ______
1 answer
(x/2)-(y/6)=-1
(x/4)+(y/12)=-3
Some people revel in working with fractions, but I find them a burden. So, get rid of all those nasty denominators. Multiply the first equation by 6, and the second by 12:
3x - y = -6
3x + y = -36
Now, add these equations and something magic happens -- the y's go away:
6x = -42
x = -7
Now, using either of the two equations, we can find y:
3x - y = -6
3(-7) - y = -6
-21 - y = -6
-y = 15
y = -15
Now, check to make sure your answer fits both of the original equations:
(x/2)-(y/6)=-1
-7/2 - (-15/6) = -1
-7/2 + 5/2 = -1
-2/2 = -1
-1 = -1
(x/4)+(y/12)=-3
-7/4 + (-15/12) = -3
-7/4 - 5/4 = -3
-12/4 = -3
-3 = -3